The implicit political satire in Ramadan television programs, exemplified by the show "Red cat." (The Peerian Journal, 2024)
Comedy is a purposeful art that possesses numerous fundamental elements in structuring events and discussing human issues, being considered a noble art with its own characteristics. The way it presents topics that carry a meaningful message revolves around provoking laughter and constructive criticism of various social issues, introducing new perspectives on subjects through satire in critique. This approach has a profound impact on both individuals and society, starting from specific objectives but extending its influence broadly, whether on political or social events.